Anthropocene [videorecording (DVD)] : the human epoch - Baichwal, Jennifer; Baichwal, Jennifer; De Pencier, Nick; De Pencier, Nick; Vikander, Alicia, 1988- (Kino Lorber, 2020)
Travels around the world exploring the impact of humans on the environment.